Estimation system using function point - Himala, Dewi Jaganathan (2013)
Software cost estimation is one of the most important parts in the project planning phase to ensure that the project will lead to success. Function point is one of the best methods used in estimating the software cost and size. Function point focuses more on measure the functionality thus make its estimation accurate and efficient. Function points features such as independent of programming language, product design and documented method makes it as an advantage. Besides measure the size and cost, function point also helps to measure the estimating the effort, schedule and defect in the project. The prototype of this research was developed using Microsoft Visual Studio 2008.